Analisis Faktor-Faktor yang Mempengaruhi Keaktifan Individu pada Komunitas Online - Rafly Ardiansyah Ikhsantyo; Diah Priharsari; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Not all online communities succeed in inviting their members to be active in them. There is a theory called "Self Determination Theory". This theory focuses on the 3 main factors that underpin an individual's experience of autonomy, competence, and relatedness is said to drive the most voluntary and high-quality forms of motivation and engagement for activities. The discipline of Information Systems is related to social phenomena that exist in society caused by the development and influence of information technology. The research was conducted by making a conceptual framework based on "Self Determination Theory" which will then provide 3 hypotheses, namely autonomy, competence, and relatedness factors that have a significant influence on individual activity in online communities. Then the data was collected through interviews conducted on 13 resource persons who are members and also administrators of the online community. The selected online community is an online community of lovers of one of the fashion products that are much favored by local and international communities. After the data was collected, qualitative data processing was carried out using descriptive coding. After analyzing the data, it was found that the factors of autonomy, competence, and relatedness have a significant influence on individual activity in online communities. Researchers also provide suggestions for online communities who want their members to be active in them.